The Effect of Storage on Potentially Synbiotic Emulsion Spread Based on Milk Fat and Inulin - Kamil Toczek; Paweł Glibowski; Monika Kordowska-Wiater; Piotr Domaradzki (Applied Sciences, 2022)
The effect of four-week storage of milk fat–inulin emulsion as a product designed for spreading on bread was analysed. The emulsion contained 20% inulin, 20% milk fat, and 2% whey protein concentrate as an emulsifier. Salt (0.2%), β-carotene (0.04%), Lactobacillus acidophilus La-5, Streptococcus thermophilus, as well as Bifidobacterium animalis BB-12 were also added. Rheological and textural analysis showed either no significant (p ≤ 0.05) or no substantial effects of storage on apparent viscosity, storage and loss modulus, hardness, cohesiveness, adhesiveness, and spreadability. The applied probiotic bacteria stayed alive at a level above 107 cfu/g during four-week storage, which is expected from a probiotic product. The whole time period of storage did not affect the chemical composition of the applied milk fat in the product. Sensory analysis showed that milk fat–inulin spread is acceptable and usually no different than commercial products, however, some off-taste and off-flavours were detected by panellists. In summary, a potentially pro-healthy product for spreading on bread was designed and studied. Besides the presence of fibre and health-promoting bacteria, the studied emulsion characterized a stable chemical composition and rheological as well as textural properties similar to commercial spreads.